Abwägung im Kommunikationsstrafrecht Strafrechtliche Verbote an der Grenze zur Grundrechtsausübung - Schallmoser, Nina Marlene (Jan Sramek Verlag, 2022)
The legislator sometimes restricts the fundamental freedoms of one person by means of criminal law in order to protect the rights of others. To this end, the legislator must weigh all the interests involved, and in criminal communications law, for example, "honor" must be set in relation to "freedom of speech". The "ideal" methodology of balancing as well as the practical handling of weighing issues are the subject of this work.